Investigation on extended care needs of patients with hypertensive intracerebral hemorrhage (高血压性脑出血患者延续性护理服务需求调查) - QIU Yajiao (邱亚娇); LIANG Hui (梁慧); WANG Fang (王芳) (中西医结合护理)
Objective To understand the extended care needs of patients with hypertensive intracerebral hemorrhage, investigate the construction methods of extended nursing service and provide reference for clinical nursing practice of hypertensive intracerebral hemorrhage. Methods Totally 150 patients with hypertensive intracerebral hemorrhage were recruited in the study, and their extended care needs were investigated by using self-made questionnaire. Results The total score of patient extended care needs assessment was (108. 29±7. 16), with an average weighted score of (3. 57±0. 68). Professional nursing, self-care and health education were most needed issues in extended care service. Conclusion Patients with hypertensive intracerebral hemorrhage have requirement of professional nursing, self-care and health education in the extended care service. An extended care plan generated by the multidisciplinary team is effective to improve the prognosis and quality of patients after discharge from hospital. (目的 了解高血压性脑出血患者延续性护理服务需求, 探讨延续性护理方案构建, 为开展延续性护理服务提供科学依据。方法 选取2020年1月—2021年6月医院收治的150名高血压脑出血患者为调查对象, 进行问卷调查。结果 对高血压性脑出血患者延续性护理服务需求调查结果进行分析, 患者延续性护理服务需求总分(108. 29±7. 16)分, 条目加权均分(3. 57±0. 68)分, 其中专业护理需求维度、自我护理需求维度和健康教育护理需求维度得分较高。结论 高血压性脑出血患者出院后对于专业护理需求维度、自我护理需求维度和健康教育护理需求较高。通过成立延续性护理小组并制定延续性护理方案, 对改善患者预后和生存质量具有重要意义。)